Seclusion: the untold legacy of the non-restraint movement in the UK. (1st April 2018) - Howe, Andrew; Sethi, Faisil
The seclusion of patients when they are an acutely high risk to themselves or others is part of psychiatric care in the UK. Seclusion was pioneered by Dr John Conolly as part of the non-restraint movement that became widespread in the UK in the 1840s. Seclusion was created out of a desire to free patients from mechanical restraints and other inhumane treatments of the day. This paper examines the emergence of seclusion as a part of the non-restraint movement. We begin by reviewing the events and practice that led to Conolly's adoption of non-restraint at Hanwell Asylum in 1839. Analysis of Conolly's thoughts on seclusion are followed by a chronological account of changes in practice to the present day. Conolly believed that seclusion was the most humane way to treat patients who were high risk to themselves and others. Seclusion was incorporated into law and its use was inspected by external investigators. The initial professional reception was positive although years later there were calls for seclusion to be abolished. It remains a controversial practice today with recent initiatives in the UK seeking to assess its efficacy. Seclusion was created not out of a want to restrict patients but to liberate them. Since its inception, its utility and purpose has been, and continues to be, assessed and reviewed. We share today the principles of wanting to improve mental health care and reduce restrictive practices with Tuke, Conolly and their contemporaries two centuries ago.